2021
DOI: 10.1177/13505084211051047
|View full text |Cite
|
Sign up to set email alerts
|

Publishing more than reviewing? Some ethical musings on the sustainability of the peer review process

Abstract: Based on our editorial experience, and acknowledging the regular editor grievances about reviewer disengagement at professional meeting and conferences, in this article we argue that the review system is in need of significant repair. We argue that this has emerged because an audit culture in academia and individual incentives (like reduced teaching loads or publication bonuses) have eroded the willingness of individuals to engage in the collective enterprise of peer-reviewing each others’ work on a quid pro q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…With Lindebaum and Jordan (2023) highlighted ethical concerns about the sustainability of the peer review system, especially concerning individuals prioritising publishing over reviewing, fostering a culture of acknowledgement and gratitude for those engaged in peer reviewing becomes essential. Here, I propose a provocative suggestion: authors submitting a manuscript to a journal should commit to reviewing two manuscripts in return.…”
Section: The Evolving Landscape Of Peer Reviewmentioning
confidence: 99%
“…With Lindebaum and Jordan (2023) highlighted ethical concerns about the sustainability of the peer review system, especially concerning individuals prioritising publishing over reviewing, fostering a culture of acknowledgement and gratitude for those engaged in peer reviewing becomes essential. Here, I propose a provocative suggestion: authors submitting a manuscript to a journal should commit to reviewing two manuscripts in return.…”
Section: The Evolving Landscape Of Peer Reviewmentioning
confidence: 99%
“…Rachel Carson’s work is only one point in case. However, more recent essays (see Lindebaum & Jordan, 2021) also attract public debate in the form of higher-than-average “Altmetric scores” and through appearance in Times Higher Education 4 shortly after online-first publication. Furthermore, some essays find their ways into practitioner/news outlets even before in-print publication (Lindebaum et al, 2020).…”
Section: Myth #2—essays Have No Extrinsic Worthmentioning
confidence: 99%
“…These developments have helped to solidify the reputation of a specific kind of peer review as necessary for data or theory to be trusted. Ironically this has happened just as a number of colleagues in management and organisation studies have suggested that double-blind peer review is founded on unrecognised and unrewarded intellectual work [and is therefore a form of exploitation of those willing to contribute anonymously to the development of others’ work, as Lund Dean and Forray ( 2018 ) argue], is hopelessly ethically problematic because it lacks transparency [and therefore reproduces specific forms of unequal power relations, as Hugh Willmott ( 2021 ) suggests 2 ], and likely to create ethically troubling inequalities (Lindebaum & Jordan, 2021 ).…”
Section: Development Editing and The Ethics Of The Peer-review Processmentioning
confidence: 99%